ANALISIS MANAJEMEN SYARIAH DALAM PELAYANAN RUMAH SAKIT UMUM DAERAH (RSUD) LEUWILIANG, KABUPATEN BOGOR - Unjaya Ulmudin; Tubagus Rifqy Thantawi; Susi Melinasari (SAHID BUSINESS JOURNAL, 2022)
The purpose of the research conducted was to analyze the guidelines and instructions for implementing services at the Leuwiliang Regional General Hospital (RSUD) in Bogor Regency, to analyze sharia management values ​​that can be applied in the services of Leuwiliang Hospital in Bogor Regency. The subjects of this study were the head of human resources and patients who came to RSUD Leuwiliang, Bogor Regency. In this study, researchers used a qualitative approach with a qualitative descriptive research type. Based on this research, it was found that the management and form of service performed by the Leuwiliang Hospital in Bogor Regency had been adjusted to government standards which were directed directly by hospital leaders to employees to provide services to patients according to the direction of the central government, namely through Law Number 25 of 2009 concerning Services Public in order to achieve consumer satisfaction with the services provided. Leaders or superiors of RSUD Leuwiliang Bogor Regency have good performance and management in managing everything, especially employees or nurses to provide good service to patients in accordance with their knowledge and guidance from leaders without losing religious values ​​and norms